Adverse Event Trends Within a Large-Scale, Routine, Voluntary Medical Male Circumcision Program in Zimbabwe, 2014–2019. (1st October 2021) - Victor, Omollo; Phiona, Marongwe; Vernon, Murenje; Thoko, Madoda; Paidamoyo, Gonouya; Farai, Gwenzi; Joseph, Hove; Munyaradzi, Tinashe; Olbarn, Rutsito; Pesanai, Chatikobo; Mufuta, Tshimanga; Vuyelwa, Sidile-Chitimbire; et al.
Abstract : Background: Between 2008 and 2020, over 22.6 million male circumcisions (MCs) were performed among men ≥10 years in 15 priority countries of East and Southern Africa. Few studies from routine MC programs operating at scale describe trends of adverse events (AEs) or AE rates over time. Setting: Routine program data from a large MC program in Zimbabwe. Methods: χ 2 compared characteristics of patients with AEs. Univariable and multivariable logistic models examined factors associated with AE severity. Cochran–Armitage trend tests compared AE rate trends by year (2014–2019), age, and MC method (2017–2019). Results: From 2014 to 2019, 469, 000 men were circumcised; of the total men circumcised, 38%, 27%, and 35% were conducted among individuals aged 10–14; 15–19; and ≥20 years, respectively. Most MCs (95%) used surgical (dorsal slit or forceps-guided) methods; 5% were device based (PrePex). AEs were reported among 632 (0.13%) MCs; 0.05% were severe. From 2015 to 2019, overall AE rates declined from 34/10, 000 to 5/10, 000 ( P -value <0.001). Severe AE rates also decreased over this period from 12/10, 000 to 2/10, 000 ( P -value <0.001). AE rates among younger clients, aged 10–14 (18/10, 000) were higher than among older age men (9/10, 000) aged ≥20 years ( P < 0.001); however, there was no significant association between age and AE severity. Conclusion: AE rates each year and over time were lower than the World Health Organization acceptable maximum (2% AEs). ZAZIC quality assurance activities ensured guideline adherence, mentored clinicians to MC competency, promoted quality client education and counseling, and improved AE reporting over time. Decreases in AE rates are likely attributed to safety gains and increasing provider experience.